A dietary sterol trade-off determines lifespan responses to dietary restriction in Drosophila melanogaster females - Brooke Zanco; Christen K Mirth; Carla M Sgrò; Matthew DW Piper (eLife, 2021)
Diet plays a significant role in maintaining lifelong health. In particular, lowering the dietary protein: carbohydrate ratio can improve lifespan. This has been interpreted as a direct effect of these macronutrients on physiology. Using Drosophila melanogaster, we show that the role of protein and carbohydrate on lifespan is indirect, acting by altering the partitioning of limiting amounts of dietary sterols between reproduction and lifespan. Shorter lifespans in flies fed on high protein: carbohydrate diets can be rescued by supplementing their food with cholesterol. Not only does this fundamentally alter the way we interpret the mechanisms of lifespan extension by dietary restriction, these data highlight the important principle that life histories can be affected by nutrient-dependent trade-offs that are indirect and independent of the nutrients (often macronutrients) that are the focus of study. This brings us closer to understanding the mechanistic basis of dietary restriction.